Evaluation of Partial Replacement of Barley Grain with Heated Potato Processing By-products in the Diet of Dairy Cows Using an In vitro Gas Production Technique - Sadq , Sarwar Mohammed; Fatehi , Farhang (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Background: The increasing urban population requires more dairy product (meat and milk) production; therefore, using agricultural sector by-products as animal feedstuffs has found double importance. Objective: The effects of replacing barley grain with heated potato slices (HPS) and French fries waste (FFW) in iso-energetic total mixed dairy cow rations on cumulative gas production and in vitro DM degradability were evaluated using in vitro techniques. Methods: Seven experimental dairy cow total mixed rations (TMR) were formulated based on partial replacing barley grain with HPS or FFW, including Control: a diet containing 16% (DM basis) barley grain as one of the main sources of non-forage carbohydrates; 5 HPS: a diet containing 11% barley grain and 5% HPS; 10 HPS: a diet containing 6% barley grain and 10% HPS; 15 HPS: a diet containing 1% barley grain and 15% HPS; 5 FFW: a diet containing 11% barley grain and 5% FFW; 10 FFW: a diet containing 6% barley grain and 10% FFW; 15 FFW: a diet containing 1% barley grain and 15% FFW. Two in vitro gas production approaches were conducted separately to measure the production of gas volumes and dry matter (DM) degradability at 2, 4, 6, 12, 24, 36, and 48 hours of incubation. Results: After 48 h of incubation, the gas production volume varied between 174 and 197 ml/g DM, with the highest value observed with control and the lowest value with FFW treatments (P < 0.05). Also, the gas production rate for the insoluble fraction varied from 0.031 to 0.054 ml/h and was higher for HPS treatments than for control and FFW treatments (P < 0.05). After 48 h of incubation, DM degradability was significantly lower for the control than other treatments. DM effective degradability, with a passage rate of 0.05 h−1, found to be higher for FFW and HPS treatments compared with the control. Moreover, the rate of the B fraction degradation was significantly lower for the control (0.14 % h−1) than for treatments. Conclusion: The heated potato processing by-products could be replaced with barley grain by 15% in the diet of dairy cows without having negative effects on ruminal fermentation.